Molecular analyses revealed three morphologically similar species of non‐native apple snails and their patterns of distribution in freshwater wetlands of Hong Kong. (17th November 2021) - Yang, Qian‐Qian; Ip, Jack Chi‐Ho; Zhao, Xing‐Xing; Li, Jia‐Nan; Jin, Yu‐Jie; Yu, Xiao‐Ping; Qiu, Jian‐Wen
Abstract: Aim: Effective control of invasive species and conservation of native biodiversity requires accurate species identification. Several species of apple snails (Ampullariidae: Pomacea ) from South America have become widespread pests in Asia since their introduction in the early 1980s, but their taxonomic uncertainty has hindered our understanding of the invasive processes. We aim to determine the identity and distribution of Pomacea species in Hong Kong, which has been known as a stepping stone of species invasion. Location: Hong Kong. Methods: We collected 162 apple snails from five freshwater wetlands of Hong Kong, sequenced the mitochondrial COI, genotyped the nuclear EF1α and built a COI dataset of 1378 sequences of apple snails from mainland China, Malaysia, Argentina and Brazil. We identified the species, determine the introgression pattern and analysed their population structures. Results: We found the co‐occurrence of P. canaliculata, P. maculata and P. occulta in Hong Kong for the first time. Pomacea canaliculata represented the dominant species (85% of collected specimens). The three Pomacea species from Hong Kong had low genetic diversity. High genetic similarity existed between P. canaliculata populations of Hong Kong and Malaysia, P. occulta populations of Hong Kong and mainland China and P. maculata populations of mainland China and Malaysia. Our samples contained a high proportion of hybrids. Main conclusions: Apple snails may have been introduced into Hong Kong multiple times: both P. canaliculata and P. occulta likely came from Argentina; P. maculata came from both Argentina and Brazil. Genetic drift largely explains the differentiation of Pomacea spp. among regions. Introgressive hybridization may have contributed to population fitness by increasing genetic variation to neutralize the founder effect. The knowledge on species identity, distribution and genetic diversity of apple snails from this study will contribute to better understanding their invasive mechanisms and prevention of their continued spread in Asia.